Peningkatan Pemahaman Mengenai Masalah Pendidikan di Wilayah Perbatasan Provinsi Nusa Tenggara Timur Pemahaman Mengenai Masalah Pendidikan di Wilayah Perbatasan Provinsi Nusa Tenggara Timur - Posma Sariguna Johnson Kennedy (CV. Multi Kreasi Media, 2022)
This activity aims to look at various educational problems in the border area of ​​the Nusa Tenggara Timur Province (NTT) and the Republic of Democratic of Timor Leste (RDTL). Implementing this activity is to conduct discussions to increase understanding of strategic issues regarding educational gaps with lecturers and postgraduate students at Nusa Cendana University, Kupang NTT. The method of writing this paper is to use a qualitative approach by reviewing various literature and quantitative data and the results of the discussions carried out. The growth in the level of education services in NTT has been increasing in line with educational investments made by the government, such as increasing the number of classrooms in senior high schools, vocational schools and universities/polytechnics. However, the average education rating in NTT is still the fourth lowest in Indonesia. The district with the worst conditions on the border is Malacca. Districts in other border areas, such as Timor Tengah Utara, Kupang and Belu, performed better than other districts. Keywords: Education Problems, Nusa Tenggara Timur, Timor Leste, Indonesian Border Region.